SOYBEAN BY-PRODUCT : AS AN ALTERNATIVE TO FISH MEAL AS PROTEIN SOURCE FOR AQUACULTURE INDUSTRY - Munir, Mohammad Bodrul (Universiti Malaysia Terengganu, 2021)
Proteins in commercial quality animal feed are one of its most important components 6 as well as one of the costliest. Currently, as a result of high costs and fluctuating production, 7 some sources of protein are unable to satiate the increasing demand from the fish feed 8 manufacturers. Fish nutrition has been accorded particular focus with less costly feedstuff in 9 aqua feed given extra weightage. There has been increasing attention in recent years on finding 10 methods to recycle the by-products of feed manufacturing. Due to its vital amino acid content 11 as well as high protein composition, soybean by-product (SBP) which is a renewable resource 12 is expected to be a viable raw material option for replacing fish meal or as a supplement. This 13 review intends to cover the information regarding SBP associated with fermentation and 14 probiotic used in aquaculture industry potentially as an alternative to replace FM.